Similarities and Differences of Honorific Systems Between Indonesian and Korean Languages (Perbedaan dan Persamaan Honorifik Bahasa Indonesia dan Korea) - Terry Chang; Yumna Rasyid; Endry Boeriswati (Jurusan Tadris Bahasa Indonesia, 2018)
This study aims to describe similarities and differences of honorific systems between Indonesian and Korean languages. The data analysis concludes that Indonesian people find it difficult to speak using Korean honorific systems. Moreover, the honorific systems in these two languages have a few similarities and differences in common, and the Korean has more complex honorific systems particularly the use of particles, verbs, vocabularies, and endings while the Indonesian has minimal honorific systems in the form of lexical markers. In addition, the Korean structure is more different from that of the Indonesian structure. Therefore, multiple ways are used to explore more honorific systems in the two languages.Â Penelitian ini bertujuan untuk mendeskripsikan persamaan dan perbedaan undak usuk dalam bahasa Indonesia dan bahasa Korea. Analisis data menyimpulkan bahwa pengguna bahasa Indonesia mengalami kesulitan ketika berbicara dengan menggunakan undak usuk bahasa Korea. Kedua bahasa ini memiliki beberapa persamaan dan perbedaan. Bahasa Korea memiliki undak usuk yang lebih kompleks. Kompleksitas dalam bahasa Korea dapat berupa penggunaan partikel, kata kerja, kosakata, dan akhiran. Adapun Bahasa Indonesia memiliki undak usuk yang minim bentuk penanda leksikal. Selain itu, struktur bahasa Korea berbeda dengan bahasa Indonesia. Oleh karena itu, berbagai cara digunakan untuk mengeksplorasi lebih banyak undak usuk dalam dua bahasa ini.